Stališča bodočih vzgojiteljic do ustvarjalnosti - Štemberger, Tina (Revija za elementarno izobraževanje, 2013)
The first part of this paper focuses on creativity, the factors that influence creativity, and on creativity in education, with a special emphasis on preschool education. In the second part, we present the results of an empirical research study in which we wanted to identify the views and positions of future preschool teachers on creativity, factors of creativity, and children's creativeness. The study showed that future preschool teachers mainly believe that not all people are creative, and neither are all children. But they believe that creative children have many opportunities to develop their creative potential in kindergarten. They consider family to be the most important factor in fostering and developing a child's creativeness.
Keywords: future preschool teacher; vzgojitelji; ustvarjalnost; creativity; predšolska vzgoja; childrens creativeness; predšolski otroci; factors of creativity